Journal of Food Quality Evaluation of Effect of Extraction Solvent on Selected Properties of Olive Leaf Extract - Won-Young Cho; Da-Hee Kim; Ha-Jung Lee; Su-Jung Yeon; Chi-Ho Lee (Journal of Food Quality)
The quest for natural preservatives and functional foods with health benefits has seen an increasing demand for natural products having therapeutic value. Herein, we investigated the influence of ethanol, methanol, acetone (50%, 70%, and 90% v/v), and distilled water on selected properties of olive leaf extract and determined the yield, total phenolic content (TPC), antioxidant activity, and antimicrobial activity. Extracts were analyzed for their oleuropein, hydroxytyrosol, and tyrosol contents by high-performance liquid chromatography (HPLC). The highest extraction yield of 20.41% was obtained when using 90 vol% methanol, while the highest total polyphenol contents of 232 and 231 mggallic-acid-equivalent/100 g were obtained for 90 vol% methanol and 90 vol% ethanol, respectively. Antioxidant activity was determined using the α,α-diphenyl-β-picrylhydrazyl (DPPH) radical scavenging assay, by determining the ferric reducing antioxidant power (FRAP), and using the Fe2+-chelating activity assay, which provided the highest values when 90 vol% methanol was used (33.84%, 0.75, and 12.91%, respectively). HPLC analysis showed that the highest oleuropein contents corresponded to the extracts obtained using 90 and 70 vol% methanol (26.10 ± 0.20 and 24.92 ± 1.22 g/L, respectively), and the highest antimicrobial activity was observed for 90 vol% methanol and distilled water. Olive leaf extracts using 90 vol% methanol had high levels of polyphenols and were highly antioxidant and antimicrobial. The results of this study facilitate the commercial applications of natural extracts with antioxidant and antibacterial activities and are expected to establish a foundation for further optimization studies.